8 - The Emergence of Public Spheres in Colonial Cameroon: The Case of Palm Wine Drinking Joints as lieux de sociabilité in Bamenda Township - Fru, Nicodemus Awesome (Africa Development, 2021)
Although Habermas might not have had Africa in mind when he pro- pounded his public sphere theory, we still find his basic premise useful in capturing the public sphere scenario in Africa where people like to periodically congregate in various sites to socialize and indulge in po- litical discourse while drinking. Using the case of colonial Bamenda township, this study examines the emergence and functioning of palm wine drinking joints as public spaces par excellence. These palm wine joints were comparable to European coffee shops and salons which were areas where various people could gather and discuss matters that concerned them. The palm wine joints were informal public spaces that emerged to respond to urbanization and cosmopolitanism, and stood out as one of the distinctive lieux de sociabilité. They were accessible to people of all classes and served as centres for drinking traditional liquor, gathering and spreading news and rumours, discussing politics and social issues, playing and dancing the ‘bottle dance’, and transiting to the ‘red streets’ to visit damsels after sucking in alcohol. The study relied on interviews and archival material as data for this article.